Reason for maternal mortality due to hypertension: an epidemiological study - Jardeliny Corrêa da Penha; Leyna Jordânia Alves da Costa; Caroline da Silva Sousa; Ana Raquel Rodrigues Rosa; Natália Santos de Almeida; Priscila de Souza Aquino (Universidad de Alicante, 2019)
Hypertension pregnancy-induced is a public health problem. Objective was to identify the maternal mortality ratio for hypertension in the years 2000 to 2013, in municipalities of the first Health Region of the State of Ceará. This´s a descriptive, retrospective and quantitative epidemiological study of secondary data, carried out from maternal deaths due to hypertension occurred between 2000 and 2013, in municipalities of the first Region of Health of the State of Ceará, obtained on the website of the Department of Informatics of the Unified Health System. Data collection took place in January 2016. 76 maternal deaths due to hypertension were identified in municipalities of the first Health Region of the State of Ceará, of which 69 (90.8%) occurred in Fortaleza-CE; 544,618 (94.6%) of the population with the highest number of live births. In 2004, 2006 and 2013, there were more records of maternal deaths due to hypertension, all with 08 cases. Eclampsia was the most prevalent among the deaths, 31 (40.7%). Maternal mortality ratio was higher in 2013, with 20.3 maternal deaths due to hypertension for 100,000 live births. Nurses and health professionals should be trained to promote quality and humanized care and thus reduce maternal morbidity and mortality rates.